Trabalho, educação e o Plano Nacional de Qualificação do Trabalhador: possibilidades ou limites? - Souza, Cristiane Gomes de (2009)
This study aims to research the National Plan of Professional Formation (PLANFOR), implemented in 1995, the logic of employability in terms of structural unemployment, with specific resources of the Fund for the Support of Workers (FAT), during the government of Fernando Henrique Cardoso and inserted into the framework of active policies Call Public Employment System. Part of understanding and qualification process that links work and education that develops and contradictory in the space between labor and capital, and the performance of the state, which divergent interests are confronted. Also focuses on changes in work under the aegis of capitalism, showing that the founding element of man and society, the work becomes an instrument of alienation of the worker, bringing therefore perverse consequences for the working class. The aim therefore is to understand the process, the design and operation of the policy PLANFOR. And for the multitude of studies and assessments on this policy, the focus of the dissertation was an attempt to systematize the main conclusions about the program in the capitalist state. Initially, we tried to outline in general all the social, political and economic as it emerged the PLANFOR to further understand it and analyze it by means of the correlation between his successor the PNQ (National Plan of Qualification). Indeed, the evidence and those policies are treated for qualification, the dominant classes, as an ideological construction that you want to create another social work compatible with their projects of class. From the perspective of workers, it is perceived as access to education and work.